Gamification, Employee And Emotional Engagement: Leveraging Gamification to Boost Employee Emotional Engagement - Kefas, Hyelda Ibrahim; Adacha Felix Kwala; Labaran Isiaku; Dokun Oluwajana; Fitzgerald Chidozie Ukaegbu; Livingston Ntiamoah Dapaa (Journal of Games, Game Art, and Gamification, 2025)
This research is aimed at critically examining the concept of gamification and its impact on human activities in the contemporary world, particularly in workplaces or organizations. During the course of the research, other vital concepts like an employee and emotional engagement will also be addressed at length. In order to achieve this aim, the research adopted the positivist philosophical approach as well as a combination of both qualitative and quantitative research. It was discovered that gamification, when applied to human activities, tends to yield a high level of emotional engagement. Similarly, the use of gamification in workplaces enhances employee engagement, competition, motivation and a high level of productivity.